Electric shock watch / Muhamad Shariful Amjad Mohd Sariff, Kamarul Azli Mohd Karno and Muhamad Haleef Mat Zin - Mohd Sariff, Muhamad Shariful Amjad; Mohd Karno, Kamarul Azli; Mat Zin, Muhamad Haleef (2013)
Due to the problems that we have faced at this UiTM these two and a half year, we have manage to make this project. With this subject, we manage to create something new to solve this problem that almost 90% student UiTM like us have this problem. The problem is to wake up at the early in the morning to attend the class and not use this as a reason to wake up too late. Now a day, student is to lazy and with only set the alarm they won’t wake. They will only stop the alarm with not really wake up, and then continue to sleep. This is the real problem to our friends. So to solve this problem we make a new invention to wake up the people from the sleep with new alarm, we also replace the alarm with the shocker circuit. For the shocker circuit we place it to human body to shock the user. For the operation to our project, firstly we use transmitter and receiver circuit to send the radio frequency and to receive the radio frequency, Radio Frequency (RF) as a medium to replace the frayed wire. For the shocker circuit we place it to receiver circuit and place the transmitter circuit at clock circuit to send the clock signal to the human body with the Radio Frequency (RF). For the conclusion to our project the Electric Shock Watch, it is a better idea because I think it will really will easy to wake up the user because of the shocker. Even if we have test, that shocker really make us feel do not want to use but it is harmless, the current that we will provide to the shocker is matching to human body.